An investigation of a price increase effect on the staple-food basket composition for low-income South African consumers - Weideman, Oelof (Faculty Commerce: Finance Administration, 2024)
The South African consumers' staple-food basket has over recent years come under pressure with unforeseen events having a detrimental impact on supply and consequently on food prices. These events have had a destabilising effect on the composition of South African staple-food baskets over the last few years. These events have been shown to have an unfavourable effect on the supply of food and consequently on the price of food. This study investigates the price-based product-switching that lowerincome South Africans practice when prices increase in their staple-food basket. Retailers and manufacturers are all reliant on a stable and predictable demand for staple foods; retailers face a missed opportunity in terms of revenue if consumers are unable to purchase a product due to it being out of stock. Manufacturers face potential monetary fines if they are unable to meet the expectations of retailers and could lose consumers and consequently revenue to competitor brands if their products are unavailable on retail shelves. Consumer-panel data from Nielsen South Africa is incorporated into the research to determine shifting in the lower-income South Africans staple-food basket consisting of maize meal, potatoes, bread and rice. The researcher assisted in the acquisition of the data, completing the entire process from the collection of raw purchase data to the development of a final data set. Due to the continuous tracking of the panel, historical trends and shifts are available to identify shifting between staple goods at times of significance. The researcher assumed a positivist paradigm and followed a quantitative approach when the panel data was analysed to determine which products households shifted from and to during times of price increases. The results and conclusions clearly define the impacts that price increases have on sales of certain products. A clear assessment was also made on the relationship between staple-food basket products, as well as consumers' tendency to switch between products in their staple-food basket. These insights enable retailers and manufacturers to efficiently plan for consumer demand before and during times of price increases in a staple-food basket.